Increasing Information Technology Literacy of Students in Sijuk 02 State Elementary School Through PowerPoint Workshop - Novario Jaya Perdana; Upie Fitri Nurqalby; Willson Steven Zebua; Grasella Aldonia Pangandaheng; Mega Sandra; Darren Melvin (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2024)
Information Technology (IT) literacy is very important and should be taught even in early education. Proper use of IT is needed by the young generations today. Introduction to IT should be done while still in elementary school. However, since the infrastructure of Indonesia is not even among the cities, a glimpse of IT is a privilege enjoyed by students in big cities. Students in smaller cities often face difficulties and tardiness regarding the use of technology. For instance, the students of SD Negeri 02 Sijuk have deficiencies in facilities and infrastructure, which causes a low level of literacy in information technology. Therefore, basic computer skill training was created to introduce the technology to its students. In this training, the students are taught to design and process text and images to create attractive presentations using Microsoft PowerPoint. The students showed very high enthusiasm when the training was carried out. In the end, through this training, the students were successfully introduced to the use of information technology.